Subsurface Characterization Based on Shear Wave Velocity for Site Classification in Earthquake Mitigation Efforts in Muara Bangkahulu - clora ulandari; Refrizon Refrizon; Halauddin Halauddin; Arif Ismul Hadi; Hana Raihana; Mesi Prasisilia; Nurul Apriyanti; Sefti Dewi Sari; Yola Dwi Rahmadhani (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2026)
Muara Bangkahulu District, Bengkulu City, is a coastal area located in an active seismic zone due to the influence of the Sumatra Subduction Zone and the Sumatra Fault. The geological conditions, which are dominated by alluvial sediments and swamp deposits, have the potential to increase earthquake wave amplification, thus requiring a study of subsurface characteristics as a basis for disaster mitigation. This study aims to identify variations in shear wave velocity (Vs30) and determine soil site classification based on the SNI 1726:2019 standard. The method used is Multichannel Analysis of Surface Waves (MASW) at ten measurement points with a track length of 50 m. The data were processed through Rayleigh wave dispersion analysis and inversion to obtain a one-dimensional (1D) model, then integrated with two-dimension al (2D) modeling to describe subsurface lateral variations. The results of the study show that the Vs30 value ranges from 137 to 450 m/s, which is divided into SE, SD, and SC site classes. The coastal area is dominated by soft to medium soil with high seismic amplification potential, while the central to eastern parts show denser and more stable soil conditions. The integration of 1D and 2D models shows a heterogeneous subsurface structure both vertically and laterally. In conclusion, the MASW method is effective in technical considerations for seismic hazard assessment, determining construction priorities, and planning foundations that are more adaptive to local soil conditions in the coastal area of Bengkulu City.